Medicaid-ing uninsurance? The impact of the Affordable Care Act's Medicaid expansion on uninsurance spells - Bradley T. Heim; Ithai Lurie; Elena Patel; Shanthi Ramnath (Federal Reserve Bank of Chicago, 2023)
We study the effect of the Affordable Care Act's Medicaid expansion on coverage dynamics following the sudden loss of coverage from an employer plan. This analysis leverages novel administrative data capturing monthly health insurance coverage for the U.S. population. Using these data, we develop several stylized facts describing the postseparation coverage dynamics. In addition, we use a difference-in-differences model to estimate the causal effect of Medicaid expansion on the duration of uninsurance following a separation from an employer plan. We find that Medicaid expansion increases the likelihood of finding coverage by 16% and reduces the duration of uninsurance by 12%.
Keywords: J65; I13; I18; I38; 330; Health Insurance Dynamics; Unemployment; Medicaid Expansion